2012
DOI: 10.1080/14623730.2012.733600
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of the psychosocial well-being of recent orphans compared with non-orphans in a school-attending cohort in KwaZulu-Natal, South Africa

Abstract: To assess differences in psychosocial wellbeing between recent orphans and non-orphans, we followed a cohort of 157 school-going orphans and 480 non-orphans ages 9-15 in a context of high HIV/AIDS mortality in South Africa from 2004 to 2007. Several findings were contrary to published evidence to date, as we found no difference between orphans and non-orphans in anxiety/depression symptoms, oppositional behavior, self-esteem, or resilience. Female gender, self-reported poor health, and food insecurity were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Unfortunately, there are no local studies with which to immediately compare our findings. Notwithstanding, selected studies in some part of sub-Saharan Africa (Northam et al, 2010; Nsereko et al, 2014; Horn, 2010; Okawa et al, 2011; DeSilva, Skalicky, Beard et al, 2012; Nsereko, Musisi, Nakigudde et al, 2014; Escueta, Whetten, Ostermann et al, 2014) have reported high prevalence psychosocial functioning problems among children and young people. In particular, in a study conducted among undergraduate university students selected from three universities in a similar setting such as Uganda, 37% of the participants were reported to have psychosocial problems and this was due to traumatic life experiences in about 49%; emotional problems in about 35%; antisocial behaviour in about 21% and academic problems in about 38% of the participants (Nsereko, Musisi, Nakigudde et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are no local studies with which to immediately compare our findings. Notwithstanding, selected studies in some part of sub-Saharan Africa (Northam et al, 2010; Nsereko et al, 2014; Horn, 2010; Okawa et al, 2011; DeSilva, Skalicky, Beard et al, 2012; Nsereko, Musisi, Nakigudde et al, 2014; Escueta, Whetten, Ostermann et al, 2014) have reported high prevalence psychosocial functioning problems among children and young people. In particular, in a study conducted among undergraduate university students selected from three universities in a similar setting such as Uganda, 37% of the participants were reported to have psychosocial problems and this was due to traumatic life experiences in about 49%; emotional problems in about 35%; antisocial behaviour in about 21% and academic problems in about 38% of the participants (Nsereko, Musisi, Nakigudde et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most research focuses on the interaction between perceived quality of support and psychological wellbeing (Cheng et al, 2014; DeSilva et al, 2012; Okawa et al, 2011; Wang et al, 2012). Perception of quality is critical for a child to feel supported and connected.…”
Section: Social Support Types and Sourcesmentioning
confidence: 99%
“…In South Africa, an estimated 20% of children (2.5 million) have lost at least one parent due to AIDS (DeSilva et al, 2012). The number of children affected by HIV is even higher (Sherr et al, 2014) and these children face additional psychological and health burdens (Betancourt, Meyers-Ohki, Charrow, & Hansen, 2013; Short & Goldberg, 2015).…”
mentioning
confidence: 99%
“…Empirical findings indicate that self-esteem and resilience are intricately linked, with associations ranging from r =.21 to r =.51 [ 18 20 ]. Self-esteem was inconsistently associated with depression/anxiety symptoms, yet higher resilience scores were linked with lower depression/anxiety symptoms [ 21 24 ] [ 25 , 26 ]. In some studies, the constructs of self-esteem and resilience are used synonymously [ 16 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%